Kendall Phelps: capstone - Phelps, Kendall, artist (Colorado State University. Libraries, 2019)
The artist's statement: As a graphic designer my work represents what projects I take on and what my client asks of me. The importance of design to me is all about problem solving and creating interesting visuals for people to see. Creating an aesthetic of what was anticipated and taking that even further is how I would describe my process of creating. My goal is always to create something that can be understood by most but has a deeper meaning. When working with clients or on a project, I like to start out with questions to narrow down the path to take. For instance, what does this project need to communicate to the viewer or what does the client explicitly not want. Then comes narrowing down which style and tone the project should encompass. By taking these steps, the idea becomes clear and understandable. After that comes rough concepts and then advanced renderings. I then like to show this to the client or advisor to get feedback on whether the design is going in the right direction. If so, I then finalize the design. I have found that this is the best process for my design process. Design has always been a big part of my life and I have always taken interest in how things visually look. Whether it be street signs or a menu at a restaurant, I have always found the design elements in my day to day life to be the most interesting. Graphic design is a passion of mine that seems to be forever evolving. I look forward to a career in design that allows me to express this passion.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design